2008
DOI: 10.1080/14622200801978730
|View full text |Cite
|
Sign up to set email alerts
|

A formative examination of messages that discourage tobacco use among junior enlisted members of the United States military

Abstract: Smoking prevalence among junior enlisted members of the United States armed forces significantly exceeds that of civilians. Furthermore, nearly 40% of junior enlisted who smoke reported they initiated smoking after joining the military. Although the tobacco industry has attempted to develop messages that encourage military members to use tobacco, no research has examined messages that would counteract industry messages and effectively discourage military members from using tobacco. This study conducted 24 focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…A number of large studies have documented a high prevalence of tobacco use in MP [3,4,[7][8][9][10], and it has been reported that many non-smokers start smoking after entering the military [10]. In our study, 5.9% of the MP claimed to have started smoking during deployment, and the less heavy smokers increased their tobacco consumption.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…A number of large studies have documented a high prevalence of tobacco use in MP [3,4,[7][8][9][10], and it has been reported that many non-smokers start smoking after entering the military [10]. In our study, 5.9% of the MP claimed to have started smoking during deployment, and the less heavy smokers increased their tobacco consumption.…”
Section: Discussionsupporting
confidence: 42%
“…The work of Hoffman and colleagues [10] offers us some cues. MP play a model role as non-smokers for children and adolescents.…”
Section: J R Armymentioning
confidence: 99%
“…These groups explored themes and messages about smoking that might be effective in promoting tobacco use prevention or cessation among junior enlisted personnel. Details of instrument development, recruitment, and procedures have been previously described 11 ; Table I outlines group characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies used indirect approaches, such as interviewing health promotion personnel and reviewing commanders' written messages, or focused on enlisted personnel. 16 20 25 26 Nevertheless, this study has some limitations. First, because of the sensitive nature of the interviews and the need to protect the interviewees' confidentiality, we collected limited demographic data and did not link interviews to the demographic characteristics of interviews, including tobacco use status.…”
Section: Discussionmentioning
confidence: 96%